PENYELENGGARAAN KETENTERAMAN DAN KETERTIBAN UMUM OLEH SATUAN POLISI PAMONG PRAJA DALAM PENEGAKAN PERATURAN DAERAH (Jurnal Konstituen, 2020)
Sometimes Municipal Police acts reactively or repressively without heed to civil rights in doing their operation. Then, Bandar Lampung government has to provide a proper place for street vendors as per local Regulation (The Law Number 8 of 2009). In order to prevent any clashes between civil service police and people in society, especially street vendors, there are several things which need to be done: (1) quality of human resource in municipal police unit need to be improved; (2) Municipal Police need to use persuasive approach in performing their job; (3) local regulation needs to be aligned; (4) local regulation has to be enforced continuously and appropriately. Keywords: civil service police function, local regulation enforcement